2005
DOI: 10.1038/sj.cgt.7700837
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical full-scale evaluation of dendritic cells transfected with autologous tumor-mRNA for melanoma vaccination

Abstract: Most cancer vaccines to date have made use of common tumor antigens or allogenic cancer cell lines. The majority of tumor antigens may, however, be unique patient-specific antigens. Dendritic cells (DCs) are the most potent antigen-presenting cells known. The present report is a full-scale preclinical evaluation of autologous DCs transfected with autologous tumor-mRNA (tDCs) for vaccination in malignant melanoma. By using autologous tumor-mRNA, we intend to make the DCs present a broad spectrum of tumor-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 27 publications
(32 reference statements)
2
52
0
Order By: Relevance
“…The nature of the immune response was not studied in detail in this clinical study, but in a preclinical evaluation, we analysed a broad range of cytokines using the Bioplex system. These results demonstrated that a broad spectrum of cytokines was produced in the in vitrogenerated T-cell response (LJ Mu et al, unpublished;Kyte et al, 2005) All of the patients who mounted a specific T-cell response also developed a component of MLR reactive cells recognising DCn. This also held true for most of the patients who failed to raise a specific T-cell component.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The nature of the immune response was not studied in detail in this clinical study, but in a preclinical evaluation, we analysed a broad range of cytokines using the Bioplex system. These results demonstrated that a broad spectrum of cytokines was produced in the in vitrogenerated T-cell response (LJ Mu et al, unpublished;Kyte et al, 2005) All of the patients who mounted a specific T-cell response also developed a component of MLR reactive cells recognising DCn. This also held true for most of the patients who failed to raise a specific T-cell component.…”
Section: Discussionmentioning
confidence: 84%
“…Selected mRNA preparations were also evaluated on an Agilent Bioanalyser instrument using RNA 6000 Nano Reagent & Supplies (Agilent Technologies, Palo Alto, CA, USA). The Bioanalyser quantifies RNA by calculating size and concentration of each separated band (Kyte et al, 2005). Transfection efficiency was monitored in separate experiments with enhanced green fluorescent protein mRNA instead of tumour mRNA as described (Mu et al, 2003).…”
Section: Preparation Of Mrna-transfected Dcsmentioning
confidence: 99%
“…Extraction of autologous tumor-RNA was performed as a two-step procedure, as previously described. 25 First, total-RNA was extracted by use of Trizol (Invitrogen Life Technologies, Carlsbad, CA). Then mRNA was purified by use of polyT-coated magnetic beads (Genoprep mRNA Beads, Qiagen, Hilden, Germany).…”
Section: Patient Inclusion and Exclusionmentioning
confidence: 99%
“…For 16 patients, the RNA samples were also evaluated on an Agilent Bioanalyser instrument (Agilent Technologies, Palo Alto, CA), as previously described. 25 The RNA concentration, rRNA percentage and mRNA content were estimated, according to the manufacturer's protocol.…”
Section: Patient Inclusion and Exclusionmentioning
confidence: 99%
See 1 more Smart Citation